Locality as a space for negotiation and resistance in local television - Rianto, Puji; Setiawati, Titin; Wahyudi, Risky; Sari, Genny Gustina; Susilo, Daniel (ProTVF, 2024)
Background: Local television has an important role in displaying local culture and identity. This role is becoming crucial amidst the dominance of Jakarta’s national television, which not only broadcasts certain cultures and groups but also tends to be biased. Purpose: This study was conducted to explain how locality is used as a means of negotiation and resistance of local television against the domination of national television. Method: This research was conducted using qualitative methods by taking local television, RBTV, part of the national television network Kompas TV, as a case. Data was collected with in-depth interviews, observations, and documents. Result: This research shows that although local television has limited broadcast time (5 hours), it creatively uses locality to negotiate and resist the domination of national television. RBTV uses three tactics to bargain its position with Kompas TV. First, they negotiate the presenter’s standard. For instance, RBTV welcomes presenters who speak at standard speed but does not accept people with oriental faces and Jakarta accents. Second, they broadcast local communities to increase engagement with the audience. Third, they broadcast local culture, such as tradition, customs, food, and fashion. Conclusion: RBTV makes the most of its time to serve and show the local community. Something that Jakarta national television cannot do well. Implications: Local television has become an “arena” for cultural battles and acts as an actor. The thesis of imperialism and cultural domination in the context of RBTV fails. This research suggests the importance of studies with a local perspective so that the dialogue between local, national and global cultures can be investigated.